Relevance of concurrent hypercalcemia in ureteric sarcoidosis complicated with bladder urothelial carcinoma: a case report - Hayashida, Michikata (BMC Nephrol, 2020)
BACKGROUND: Sarcoidosis is a multisystem inflammatory disorder and can affect any organ; however, ureteric involvement is extremely rare with only four cases reported in the literature to date, all of which were diagnosed with surgical ureteral resection including a nephroureterectomy. This study reports the first case of ureteric sarcoidosis controlled with medical therapy where a differential diagnosis was performed based on the diagnostic clue of hypercalcemia. A definitive diagnosis was established without surgical resection of the ureter. CASE PRESENTATION: A 60-year-old man presented with anorexia and weight loss. Blood tests showed renal dysfunction and hypercalcemia. Computed tomography revealed left hydronephrosis associated with left lower ureteral wall thickening, which showed high signal intensity on diffusion-weighted magnetic resonance imaging. Similarly, we detected a bladder tumor on cystoscopy, and a 2-cm-long stenosis was revealed by retrograde ureterography; therefore, ureteral cancer was suspected. Meanwhile, considering the clinical implication of hypercalcemia, a differential diagnosis of sarcoidosis was established based on elevated levels of sarcoidosis markers. Fluorodeoxyglucose positron emission tomography showed fluorodeoxyglucose accumulation in the left lower ureter, skin, and muscles, suggestive of ureteric sarcoidosis with systemic sarcoid nodules. For a definitive diagnosis, transurethral resection of the bladder tumor and ureteroscopic biopsy were performed. Histopathological examination revealed ureteric sarcoidosis with bladder urothelial carcinoma. Following an oral administration of prednisolone, hypercalcemia instantly resolved, the renal function immediately improved, and the left ureteral lesion showed complete resolution with no recurrence. CONCLUSIONS: In this case, the co-occurrence of ureteral lesion with bladder tumor evoked a diagnosis of ureteral cancer. However, considering a case of ureteral lesion complicated with hypercalcemia, assessment for differential diagnosis was performed based on the calcium metabolism and sarcoidosis markers. In cases of suspected ureteric sarcoidosis from the assessment, pathological evaluation with ureteroscopic biopsy should be performed to avoid nephroureterectomy.